Climate change and vascular plant species interactions on sub-Antarctic Marion island - Le Roux, Peter Christiaan (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Conservation Ecology and Entomology))--Stellenbosch University, 2008.